Minerais de ferro do Ordovícico Inferior do Anticlinal de Valongo - H. Couto (2011)
The Lower Ordovician oolitic ironstones of Valongo anticline have abundant chamosite and/or siderite. True oolites are rare in the studied levels. Some pseudo-oolites are related to the presence of algae, as evidenced by cathodoluminescence. Iron came from emerged areas and deposited during transgression of Early Ordovician, in a shallow platform protected by barriers, with exhalativesedimentary vent in reducing environment rich in organic matter